Synthesis and Characterisation of Lanthanide Nicotinates and Their Mixed Complexes Using Dimethylglyoxime, Salicylaldoxime and Pyridine-2-aldoxime as Secondary Ligands - Pande, M.V.; Ramachandra Rao, V. (Asian Journal of Chemistry, 2010)
Simple complexes of the type Ln(L)3 and mixed complexes of the type Ln(L)3(L´)·nH2O where Ln = Y(III), La(III), Pr(III), Nd(III), Sm(III), Gd(III) and Dy(III), L = nicotinic acid, L´ = dimethylglyoxime, salicylaldoxime, pyridine-2-aldoxime and n = 2 or 3 have been prepared and characterised by a study of elemental analysis, electronic spectra, infra red spectra, thermoanalytical and conductivity measurements. The nmr spectra of La(III), Pr(III) and Dy(III) nicotinates and their mixed complexes have been recorded to elucidate the changes in chemical shift observed by these ions. A coordination number six and eight is suggested for the several lanthanide ions in simple and mixed complexes respectively.